Kesantunan Berbahasa dalam Sinetron Ikatan Cinta: Kajian Pragmatik - Anak Agung Nita Yuliantari; I Wayan Simpen; I Gusti Ngurah Ketut Putrayasa (Stilistika : Journal of Indonesian Language and Literature, 2022)
This research is entitled "Language politeness in the soap opera Ikatan Cinta: Pragmatic Studies". The purpose of this study was to determine the principle of politeness in language and the factors that cause politeness in the language in the soap opera "Ikatan Cinta". The theory used in this research is a pragmatic theory that includes the principle of politeness in language proposed by Leech. This study requires qualitative data to analyze the speech of the protagonist and the characters in the soap opera "Ikatan Cinta". The data collection method used is the listening method with the free-of-conversation listening technique. The process of data analysis used descriptive qualitative methods while presenting the results of the data analysis used formal and informal methods. The source of this research data used as material for analysis is the speech of the protagonist and the character in the soap opera "Ikatan Cinta" which can be found in the Vision+ application. The results of this study are in the form of the principles of language politeness and the factors that cause language politeness contained in the speech between the characters of the soap opera "Ikatan Cinta". The principle of politeness found in the soap opera "Ikatan Cinta" is tact maxim, generosity maxim, approbation maxim, agreement maxim, modesty maxim, and sympathy maxim. This study found the factors that cause politeness in the soap opera "Ikatan Cinta", namely the status factor, age factor, and gender factor. Of the three factors, the most commonly found in the status factor.